Defying fraternity: Woman as citizen in Germaine de Stael's Corinne, or Italy. - Marso, Lori J. (Women's Studies)
Explores the influence of politics on gender boundaries in France as depicted in the book `Corinne, or Italy,' by Germaine de Stael. Influence of history on feminism; Profile and influences of de Stael; Book as a criticism of the French revolution; Plot and characters of book.